Transnational discursive opportunities and social movement risk frames opposing GMOs - Campos Motta, Renata (Social movement studies, 2015)
Research on social movement frames has been cumulative. Recently, scholars started studying the structural incentives and constraints for claim-makers by relying on the concept of discursive opportunity structure (DOS) while bringing the public sphere and the media to the centre of analysis of political contention. This article draws on these literatures to investigate social movement campaigns against genetically modified (GM) crops and pesticides in Argentina, Brazil and Mexico. First, it argues that there is a transnational DOS that provides structural incentives and constraints to frame risks in symbolic struggles to define GM crops. Next, based on a content analysis of national newspapers, it describes the use of risk frames in national public discourses. Finally, it addresses the question of how this transnationalized DOS is framed by the media by looking at the discursive opportunities for social movements as well as other collective actors in their framing disputes. The study provides evidence of a transnationalization of public debates and offers explanations for national variations by resorting to other components of the DOS such as national policy discourse, timing of political agendas, media structure and culture. It concludes by recognizing the need to consider the various dimensions of opportunity structures for movement action, i.e. political, discursive, and economic, and their relative degree of transnationalization or autonomy over global forces.